Benevolent Theodicies Protect Against PTSD Following a Natural Disaster - McElroy, Stacey E. (Journal of psychology and christianity, 2018)
Natural disasters are potentially traumatic events that can violate survivors' beliefs about the world and lead to the development of Post-Traumatic Stress Disorder (PTSD). Given that natural disasters are increasing in frequency and intensity, it is important to identify factors that can help protect survivors from negative mental health outcomes such as PTSD. In this study, adult survivors of the 2016 Louisiana flood (N = 466) completed measures of belief violations, benevolent theodicies, and post-disaster PTSD symptoms. We hypothesized that belief violations would be positively related to PTSD symptoms, but this relationship would be buffered when survivors believed God (a) has providential control over suffering (providence theodicy), (b) suffers along with them (suffering-God theodicy), and (c) uses suffering to build people's character and virtues (soul-building theodicy). Results supported these hypotheses. Belief violations were positively related to PTSD symptoms, yet belief in benevolent theodicies buffered this relationship. Implications are discussed in terms of disaster preparedness and relief, including recommendations for disaster ministry and spiritual first aid.